Alternative Model of Settlement of Narcotics Abuse by Children through Diversion (Case Study in Sambas District) - Salam, Malik Abdus; Oktarina, Tri Nurmega (Universitas Negeri Semarang, 2019)
This case discusses about in narcotic narcotics version of child (case study in district of execution of diversion against child of perpetrator of narcotics crime pursuant to law no 11 year 2012 about juvenile criminal justice system from position of law of diversion to child abuse of narcotics in developmental perspective criminal law is a non-panel policy measure for handling child perpetrators of child criminal acts as their handling is transferred to the juvenile justice system. Related to the handling of children of narcotics abuse, the main problem that arises from the criminal justice process of a child or criminal decision is the stigma attached to the convict of narcotics abuse after the completion of the criminal justice process tends to increase the abuse of narcotics conducted by the child. the diversi- fication concept set forth in the Indonesian justice system is putting the obligation to divert in any judicial proceedings (investigation, prosecution, trial) of the diversion settings against the perpetrators, the future narcotics crime concept of implementation is only a component and improved the structure of the Juvenile justice system as an alternative to formal criminal justice by placing diversionary efforts in every stage of the judicial process (investigation, prosecution and civil law). future divergence concepts not only as an alternative to the just legal system but the diversion that really excludes the process.